1991
DOI: 10.1177/017084069101200302
|View full text |Cite
|
Sign up to set email alerts
|

Chinese Conflict Preferences and Negotiating Behaviour: Cultural and Psychological Influences

Abstract: This paper analyzes the extent to which both traditional Chinese cultural values and Chinese psychology influence Chinese perceptions and approaches to conflict resolution and thus affect Chinese negotiating behaviour. An attempt is made to illustrate salient cultural values and orientations, and empirical data is used to identify Chinese conflict preferences. The extent to which both these cultural values and conflict preferences have shaped a distinctive Chinese negotiation style is then examined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
228
6
2

Year Published

1996
1996
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 359 publications
(251 citation statements)
references
References 32 publications
15
228
6
2
Order By: Relevance
“…According to Yuen, Asian societies stress collectivism, 'face' and harmony; and the 'preferred conflict-resolution styles are likely to be compromising (the middle ground, with neither side having to suffer a loss of ''face''), avoiding (not address the conflict, a strategy used to avoid a possible loss of ''face'') or collaborating (satisfy the concerns of both parties), (Yuen, 1992: 376). Kirkbride et al (1991) investigated the conflict styles of 981 Chinese respondents in Hong Kong, and the findings have confirmed the researchers' predictions based on Chinese cultural values. They have found that the conflict management styles of the Chinese in Hong Kong are, in order of preference: compromising, avoiding, accommodating (satisfy the other party's demands even at the expense of his/her personal concerns), collaborating and competing (pursue his/her own concerns at the expense of the other party).…”
Section: Comparing Hong Kong Contestants' Behaviour In Both Hong Kongsupporting
confidence: 62%
“…According to Yuen, Asian societies stress collectivism, 'face' and harmony; and the 'preferred conflict-resolution styles are likely to be compromising (the middle ground, with neither side having to suffer a loss of ''face''), avoiding (not address the conflict, a strategy used to avoid a possible loss of ''face'') or collaborating (satisfy the concerns of both parties), (Yuen, 1992: 376). Kirkbride et al (1991) investigated the conflict styles of 981 Chinese respondents in Hong Kong, and the findings have confirmed the researchers' predictions based on Chinese cultural values. They have found that the conflict management styles of the Chinese in Hong Kong are, in order of preference: compromising, avoiding, accommodating (satisfy the other party's demands even at the expense of his/her personal concerns), collaborating and competing (pursue his/her own concerns at the expense of the other party).…”
Section: Comparing Hong Kong Contestants' Behaviour In Both Hong Kongsupporting
confidence: 62%
“…Building upon the assumption that individual preferences in general (e.g., Bowles, 1998) and individual preferences of handling conflicts in particular (e.g., Elsayed-EkJiouly & Buda, 1996;Kirkbride, Tang, & Westwood, 1991;Ting-Toomey et al, 1991;Wang, Lin, Chan, & Shi, 2005) are culture specific, we develop hypotheses that link cultural value dimensions to the general tendency that an individual prefers some conflict handling styles over others. In the literature several concepts of culture are present to understand and measure the effect of culture on various outcomes (e.g., Hofstede, 1980;Hofstede, Hofstede, & Minkov, 2010;House et al, 2004;Inglehart, 1997;Schwartz, 1994Schwartz, , 2006Triandis, 1995;Triandis & Gelfand, 1998).…”
Section: National Culture and Conflict Handling Stylesmentioning
confidence: 99%
“…Second, Chinese people emphasize the importance of emotional control, maintenance of politeness, and avoidance of aggressive persuasion techniques in Social Problem Solving and Well-Being 6 conflict negotiation (Shenkar & Ronen, 1987). As a result, Chinese people are much more likely to use avoidance, compromise, and tolerance when handling conflicts, rather than applying the problem-solving strategies of conflict management (Allison, 1997;Kirkbride et al, 1991). Third, the hierarchical nature of Chinese families can be a major barrier to the application of problem-solving skills in family relationships.…”
mentioning
confidence: 99%